Company law 12 edition - Dignam, Alan; Lowry, John (New York : Oxford University Press, 2022)
"us so. There are two reasons for this. First, company law has become a quasi-core subject with students choosing it because they regard it, not unnaturally, as an essential requirement for pursuing a career as a commercial lawyer. The fact that many students may not have the skills best suited to studying company law never seems to put students off and is often at the root of a poor to mediocre performance in the exams. So what are the essential skills needed? A good knowledge of contract, a proper understanding of equity, good statutory and common law interpretation skills, and a certain flexibility of mind needed to deal with the legal creation of corporate personality. With this base of skills a student will be equipped to deal with the hazardous waters of company law. If you think you don't have these essential skills then put this book down and rethink your options. Choose subjects based around the skills you have already identified as your strongest. It is best to do this now rather than suffer through an unhappy year of company law"--